2010 IEEE Globecom Workshops 2010
DOI: 10.1109/glocomw.2010.5700305
|View full text |Cite
|
Sign up to set email alerts
|

On the detection of elderly equilibrium degradation using multivariate-EMD

Abstract: International audienceThe aim of this paper is to provide a new methodology for the detection of an increased risk of falling in community-dwelling elderly. A new extended method of the empirical mode decomposition (EMD) called multivariate-EMD is employed in the proposed solution. This method will be mainly used to analyze the stabilogram center of pressure (COP) time series. In this paper, we describe also the remote non-invasive assessment method, which is suitable for static and dynamic balance. Balance wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The prediction or warning of falling events, which can result in life-threatening injuries for elderly individuals such as fractures and visceral ruptures, is highly desired in elderly support services [ 141 , 142 , 143 , 144 ]. Gait information, including CoP displacement, total CoP displacement, step length, and gait velocity, is considered important for detecting falls [ 145 , 146 ]. These parameters are explained in Table 8 and Section 6.1 .…”
Section: Six Chronic Diseases and Corresponding Insole Systemsmentioning
confidence: 99%
“…The prediction or warning of falling events, which can result in life-threatening injuries for elderly individuals such as fractures and visceral ruptures, is highly desired in elderly support services [ 141 , 142 , 143 , 144 ]. Gait information, including CoP displacement, total CoP displacement, step length, and gait velocity, is considered important for detecting falls [ 145 , 146 ]. These parameters are explained in Table 8 and Section 6.1 .…”
Section: Six Chronic Diseases and Corresponding Insole Systemsmentioning
confidence: 99%
“…Due to the high flexibility and sensitivity of conductive ink films, PSD sensors fabricated with these inks can replace traditional PSD devices such as force plates. These sensors can be applied for diagnosing falling events, knee osteoarthritis (KOA), and similar diseases by detecting subtle pressure changes and deviations in the center of pressure (CoP) [ 66 , 67 , 68 ]. For instance, the conductive ink film-based PSD insole system proposed by Zhao et al contains forty-eight sensors, as shown in the Figure 5 .…”
Section: Comparison and Review Of Piezoresistive And Piezoelectric Ps...mentioning
confidence: 99%
“…The prediction or warning of falling events, which may cause elder people life-threatening injuries, such as fractures and visceral rupture, is strongly expected in elderly support services [102][103][104][105]. The concerned gait information for falling detection include CoP displacement, total CoP displacement, step length, and gait velocity [106,107]. Note that, the CoP refers to the pressure center of a single foot at the walking or standing state, while CoP emphasizes the pressure center of both feet during the standing posture.…”
Section: F Elder Falling Eventmentioning
confidence: 99%